2017
DOI: 10.1097/shk.0000000000000752
|View full text |Cite
|
Sign up to set email alerts
|

Burn Injury Alters Epidermal Cholinergic Mediators and Increases HMGB1 and Caspase 3 in Autologous Donor Skin and Burn Margin

Abstract: Burn wound healing complications, such as graft failure or infection, are a major source of morbidity and mortality in burn patients. The mechanisms by which local burn injury alters epidermal barrier function in autologous donor skin and surrounding burn margin are largely undefined. We hypothesized that defects in the epidermal cholinergic system may impair epidermal barrier function and innate immune responses. The objective was to identify alterations in the epidermal cholinergic pathway, and their downstr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
11
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 28 publications
0
11
0
Order By: Relevance
“…Cell stress, such as UV irradiation, can result in mitochondrial release of cytochrome c and APAF 1, which recruit procaspase 9, forming the apoptosome and subsequently activating caspase 9 [ 26 ]. While the involvement of the initiator caspase 9 has not been studied in thermal injury, Holmes et al were able to detect the executioner caspase 3 after thermal stress in vitro, indicating a caspase-dependent pathway in thermally injured keratinocytes [ 27 ].…”
Section: Apoptosis Of Keratinocytes In Vitromentioning
confidence: 99%
“…Cell stress, such as UV irradiation, can result in mitochondrial release of cytochrome c and APAF 1, which recruit procaspase 9, forming the apoptosome and subsequently activating caspase 9 [ 26 ]. While the involvement of the initiator caspase 9 has not been studied in thermal injury, Holmes et al were able to detect the executioner caspase 3 after thermal stress in vitro, indicating a caspase-dependent pathway in thermally injured keratinocytes [ 27 ].…”
Section: Apoptosis Of Keratinocytes In Vitromentioning
confidence: 99%
“…Many other downstream pathways may involve α7 nAChRs and TLR4 interaction, such as overexpression of IL-1 receptor-associated kinase M (IRAK-M), a negative regulator of TLR4, in macrophages resulted in decreased TNF-α production through a Jak2-STAT3 signaling pathway by α7 nAChR activation [ 82 ]. HMGB1, a cytokine mediator of inflammation, has been reported to upregulate α7 nAChR expression [ 83 ]. In addition, vagus nerve stimulation or cholinergic receptor agonists have been suggested to inhibit the activation of NACHT, LRR, PYD domains-containing protein 3 (NLRP3) inflammasome, a key modulator of innate immunity, whereas genetic deletion of α7 nAChR enhances inflammasome activation.…”
Section: Introductionmentioning
confidence: 99%
“…In addition, HMGB-1 staining may be useful for visualizing burn progression, as the initially healthy area of tissue surrounding the burn eventually becomes non-viable due to expansion of the necrotic zone [14, 16]. A recent study has also suggested a link between HMGB-1 and cholinergic activation, as alterations in cholinergic mediators are associated with the induction of HMGB-1 after burn injury [17].…”
Section: High Mobility Group Box-1 (Hmgb-1)mentioning
confidence: 99%